EQUIPMENT SALES SYSTEM IN STORES ABC OLAGRAGA USING ACCESS SPORT - Armel Gustian; Don Syafitra, Ir (Jurnal Sistem Informasi, 2002)
Data search and data entry, data and consumer goods can be done quickly as well tofacilitate data processing section to perform the above processes, analyzing data onexercise equipment sales system can be done quickly and akurat.Mengingat in thebusiness world strongly consider w3aktu, then with computerized data processingdone to improve work efficiency.